Changing things around: Dramatic aspect in the Pericope Adulterae (Jn 7:53–8:11) - Piet van Staden (HTS Teologiese Studies/Theological Studies, 2015)
In this article the transactional model of narrative as expounded by Louise Rosenblatt, supported by an analysis in terms of dramatic aspect, is employed to show how the interpolated scene in John 7:53–8:11 (known as the Pericope Adulterae and hereafter referred to as PA) functions as a pivot of power in the gospel. The content of the scene, as well as its placement within the gospel, serves to promote an aesthetic reading that focusses attention on the experience during the reading event. Awareness of sensations, images, feelings and ideas from past experiences, as well as the sounds and rhythms of the words become important. The reader responds to the aesthetic transaction, the various elements of total experience, rather than simply to the text, during and after the reading event.